PROMOTING LEARNING SKILLS (4Cs) IN THE ENGLISH CLASSROOM - Balzhanova, А.М. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
The article explores the issue of developing students` learning skills (4Cs): critical thinking, communication, collaboration, creativity. These skills are included in the list of competencies of 21st century and students also need these skills to succeed in their future professional life. The special role is given to knowledge of foreign language that is considered to be one of the tools for enhancement of professional knowledge and opportunities. The article presents some techniques to support developing students` learning skills (4Cs) at English classes.
Keywords: education; foreign language; learning skills (4Cs); critical thinking; communication skills; creativity